PENGARUH CAPITAL ADEQUACY RATIO (CAR) DAN JUMLAH ASET TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA PERIODE 2020-2021 - Lara Asmara; Bayu Wulandari (STKIP Subang, 2024)
This study evaluates the impact of Capital Adequacy Ratio (CAR) and total assets on the stock value of banking companies during the period 2020-2021. A total of 88 samples were selected from the Indonesia Stock Exchange website (www.idx.co.id) by applying the purposive sampling method, which selects samples based on appropriate specific criteria. The t and F tests were applied to measure the effect of CAR and total assets variables on stock value. The t test is used to assess the impact of each variable individually, while the F test assesses the combined impact of both variables. Documentation, collecting secondary data available from reliable sources is used as the data method used. The findings show that CAR has a negative but not high impact on stock value, which means that the correlation is not strong enough. On the other hand, total assets have a high positive impact on stock value, indicating that banks with larger assets tend to have higher stock values. Furthermore, when CAR and total assets are tested together, the results show no high impact on stock value, indicating that the combination of CAR and total assets does not have a significant effect on the stock value of banking companies during the study period.